Bone cement flow analysis by stepwise injection through medical cannulas. Issue 12 (December 2016) - Zderic, Ivan; Steinmetz, Philipp; Windolf, Markus; Richards, R. Geoff; Boger, Andreas; Gueorguiev, Boyko
Highlights: Cement flow through medical cannulas is predictable and can be excluded as a source of risk for leakage during vertebroplasty. Peak injection force and cement viscosity at this force correlate significantly. Abstract: Cement leakage is a serious adverse event potentially occurring during vertebroplasty. Pre-operative in-silico planning of the cement filling process can help reducing complication rates related to leakage. This requires a better understanding of the cement flow along the whole injection path. Therefore, the aim of the present study was to analyze bone cement flow behavior by stepwise injections through medical cannulas. Sixteen cannulas were assigned to four groups for stepwise injection of differently colored cement portions of 1 ml volume. Each group differed in the amount of injected cement portions with a range of 1–4 ml. After cement curing longitudinal cross-sections of the cannulas were performed and high-resolution pictures taken. Based on these pictures, quadratic polynomial interpolation was applied to the marked intersections between the last two injected cement portions to calculate the leading coefficients. Leading coefficients in the groups with three cement portions (0.287 ± 0.078), four portions (0.243 ± 0.041) and two portions (0.232 ± 0.050) were comparable and significantly higher than the group with one cement portion (0.0032 ± 0.0004), p ≤ 0.016. Based on these findings, cement flow through medical cannulas can be considered as predictable and can therefore be excluded as a source of risk for possible cement leakage complications during vertebroplasty procedures.